Cytotoxic and apoptotic properties of silver chloride nanoparticles synthesized using Escherichia coli cell-free supernatant on human breast cancer MCF 7 cell line - Razieh Bigdeli; Masoumeh Shahnazari; Erfan Panahnejad; Reza Ahangari Cohan; Aziz Dashbolaghi; Vahid Asgary (Artificial Cells, Nanomedicine, and Biotechnology)
Synthesis of silver and silver based nanoparticles using microorganisms has received profound interest because of obtaining nanoparticles with unique physicochemical and biological properties. In the current study, for the first time, synthesis of silver chloride nanoparticles (AgClNPs) using cell-free supernatant of Escherichia coli culture is reported. Prepared AgClNPs were characterized by EDS, XRD and FESE. Data revealed the synthesized nanoparticles, mostly, have a spherical shape with an average size of 13 nm. Additionally, MTT assay elucidated a dose-dependent cytotoxicity of AgClNPs against MCF-7 cells (IC50 = 44 µg/mL). Quantitative real-time reverse transcription-PCR and colourimetric assays were employed to investigate the mechanism of cell toxicity in several cell death pathways. The results revealed the ability of AgClNPs to upregulate Bax/Bcl-2 ratio and p53 at mRNA level. Moreover, other apoptotic factors such as caspase-3, 8 and 9 were also upregulated at both mRNA and proteome levels. Finally, apoptosis induction was confirmed by Annexin-V/PI detection assay. Based on the obtained data, biosynthesized AgClNPs using E. coli cell-free supernatant exhibit a cytotoxic effect on human breast cancer cells through up-regulation of apoptotic factors, which suggest them as anti-tumour agents for further investigations.